Influence of shading by maize plants on leaf anatomy of bean of different growth habits. I. Stomata and trichomes - Silva, Heloisa Torres da; Rodrigues, João Domingos; Costa, Joaquim Geraldo Cáprio da (Pesquisa Agropecuaria Brasileira, 2014)
The types and density of stomata and trichomes were studied in leaves of bean (Phaseolus vulgaris L.) cultivars with determinate (Canário 101) and indeterminate (Rio Tibagi and Costa Rica 1031) growth habits, grown under different light intensities determined by shading by maize plants. The cropping systems were: dried plants of maize cut at 10 cm from the soil surface, plants doubled over below the first ear and upright plants. The evaluations were made at the basal, median and apical regions, and on the abaxial and adaxial surfaces of the central leaflet of the third trifoliolate leaf. Measurements of photosynthetically active radiation (PAR) were taken weekly at different heights within the bean plant canopy. The cropping systems with doubled over and upright maize plants caused a decrease in the total incident radiation. The stomatal density in all three cultivars increased with PAR. Across cropping systems, the abaxial surface showed a higher stomatal density than the adaxial, and the median region showed a higher density than the basal. The density of hooked and glandular trichomes on the abaxial surface was more affected by the available radiation than on the adaxial. Higher levels of radiation increased the density of these trichomes, and there were no effects on the straight trichomes. Canário 101 showed a higher density of hooked trichomes plasticity than Rio Tigabi and Costa Rica 1031.
Keywords: density; leaf surface; photosynthetically active radiation (PAR); cropping systems; shading; bean